2014
DOI: 10.3892/ol.2014.1981
|View full text |Cite
|
Sign up to set email alerts
|

Primary osteosarcoma of the breast: A case report

Abstract: Osteosarcoma (OS) located in the breast is an extremely rare, malignant neoplasm. The current study presents the diagnostic process, treatment and follow-up of a 67-year-old female with OS of the breast. The diagnosis was made according to diagnostic imaging methods and microscopic examination with additional immunohistochemical staining. As a surgical treatment, tumourectomy with intraoperative histological examination and simple breast amputation was performed. No adjuvant chemotherapy was administered follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Surgery in the form of wide excision aimed at achieving negative margins remains the cornerstone of management of primary breast osteosarcomas. [ 1 3 7 8 9 10 11 ] Lymph node dissection is not indicated, except when clinically involved. The effectiveness of adjuvant radiotherapy and chemotherapy however remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery in the form of wide excision aimed at achieving negative margins remains the cornerstone of management of primary breast osteosarcomas. [ 1 3 7 8 9 10 11 ] Lymph node dissection is not indicated, except when clinically involved. The effectiveness of adjuvant radiotherapy and chemotherapy however remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used either singly or in combination by various authors in an attempt to reduce the local and systemic recurrences. [ 8 9 ] The prognosis of breast osteosarcomas unlike breast sarcomas and breast carcinomas is poor. [ 9 ] Primary breast osteosarcomas are considered to be highly aggressive neoplasms with early recurrences and propensity for hematogenous spread, the 5-year survival rate has been reported at a dismal 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs (including, doxorubicin, cyclophosphamide and cisplatin) may prolong survival in patients exhibiting primary osteosarcoma; however, this has not been demonstrated in cases of breast osteosarcoma (11,16,17). In the present case, liposomal doxorubicin and cisplatin chemotherapy were selected for treatment of the patient, and an SD response evaluation was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that the tumor arises from totipotent mesenchymal cells of the breast stroma or the transformation of a preexisting fibroadenoma or phyllode tumor [2,[5][6][7]. Unfortunately, primary breast osteosarcoma is considered a poor prognosis cancer with early tumor recurrence and a propensity for hematogenous rather than lymphatic spread most commonly to the lungs [7][8][9]. We present the case of a 65-year-old Caucasian woman who was diagnosed with an osteosarcoma in her right breast.…”
Section: Introductionmentioning
confidence: 99%